2013
DOI: 10.1371/journal.pntd.0002243
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phenotypic Characterization of Manufacturing Seeds for a Tetravalent Dengue Vaccine (DENVax)

Abstract: BackgroundWe have developed a manufacturing strategy that can improve the safety and genetic stability of recombinant live-attenuated chimeric dengue vaccine (DENVax) viruses. These viruses, containing the pre-membrane (prM) and envelope (E) genes of dengue serotypes 1–4 in the replicative background of the attenuated dengue-2 PDK-53 vaccine virus candidate, were manufactured under cGMP.Methodology/Principal FindingsAfter deriving vaccine viruses from RNA-transfected Vero cells, six plaque-purified viruses for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 27 publications
5
67
0
Order By: Relevance
“…In Vero cells, a cell line usually employed for DENV quantification and for the development and production of DENV vaccines [80][81][82], alternative internalization routes can be used depending on the virus serotype. By treatment with biochemical inhibitors and overexpression of cellular proteins involved in the different endocytic routes, it was proved that the entry of DENV-1 for a productive infection requires clathrin-mediated endocytosis, whereas the infectious entry of DENV-2 into Vero cells occurs by a nonclassical endocytic pathway independent of clathrin, caveolae and lipid rafts, but dependent on dynamin [74].…”
Section: • • Internalization: Endocytic Routesmentioning
confidence: 99%
“…In Vero cells, a cell line usually employed for DENV quantification and for the development and production of DENV vaccines [80][81][82], alternative internalization routes can be used depending on the virus serotype. By treatment with biochemical inhibitors and overexpression of cellular proteins involved in the different endocytic routes, it was proved that the entry of DENV-1 for a productive infection requires clathrin-mediated endocytosis, whereas the infectious entry of DENV-2 into Vero cells occurs by a nonclassical endocytic pathway independent of clathrin, caveolae and lipid rafts, but dependent on dynamin [74].…”
Section: • • Internalization: Endocytic Routesmentioning
confidence: 99%
“…Takeda Pharmaceuticals is developing a tetravalent chimeric dengue vaccine candidate by introducing DENV-1, -3, and -4 prM and E genes into cDNA derived from a live attenuated DENV-2 component [44][45][46][47][48][49][50][51][52]. A Phase 1 dose-escalation trial in DENV-nonimmune subjects, involving a single dose of vaccine formulations with low or high DENV viral concentrations administered SQ or intradermally (ID), demonstrated acceptable safety.…”
Section: Clinical Developmentmentioning
confidence: 99%
“…The principal attenuating mutations in the DENV-2 backbone common to each component of DENVax include mutations in position 57 of the 5 UTR, residue 53 of NS1, and residue 250 of NS3 (58). Analysis of the genetic stability of the four components of DENVax during the preparation of master viral seed stocks revealed that the two attenuating mutations in the nonstructural proteins were stable: Low levels of reversion were noted with the UTR mutation (59). Clinical studies of two-dose regiments of DENVax are underway in the United States, Central and South America, and Asia.…”
Section: Live-attenuated Vaccinesmentioning
confidence: 99%